2011
DOI: 10.1021/jp110737q
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Expansivity of Ionic Clathrate Hydrates Including Gaseous Guest Molecules

Abstract: Although thermal expansion is a key factor in relation to the host-guest interaction of clathrate hydrates, few studies have investigated the thermal behavior of ionic clathrate hydrates. The existence of ionic species in these hydrates creates a unique host-guest interaction compared to that of nonionic clathrate hydrates. It was revealed that X-ray diffraction cannot be used for research of tetramethylammonium hydroxide clathrate hydrates due to damage of the cations by the X-ray, which results in abnormal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The simulation results are close to the experimental values of ionic clathrate hydrates, including gaseous guest molecules in a similar temperature range. 98 Although the trend of thermal expansion with increased temperature is similar to that for the linear expansion of sI hydrates by experimental measurements 21,98 (Fig. 10), the calculated thermal expansion coefficients of 100% sI hydrates at atmospheric pressure in this work are much greater than the experimental values of non-ionic (the conventional gas hydrates) sI hydrates (B70-110 Â 10 À6 K À1 at 180-280 K).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The simulation results are close to the experimental values of ionic clathrate hydrates, including gaseous guest molecules in a similar temperature range. 98 Although the trend of thermal expansion with increased temperature is similar to that for the linear expansion of sI hydrates by experimental measurements 21,98 (Fig. 10), the calculated thermal expansion coefficients of 100% sI hydrates at atmospheric pressure in this work are much greater than the experimental values of non-ionic (the conventional gas hydrates) sI hydrates (B70-110 Â 10 À6 K À1 at 180-280 K).…”
Section: Discussionsupporting
confidence: 70%
“…21 The values are relatively close to those of ionic sI hydrates including gaseous guest molecules (B110-244 Â 10 À6 K À1 at 180-280 K). 98 In the same way, the specific heat capacities calculated by our simulations also exhibit an obvious discrepancy with the experimental values below 260 K (Fig. 12).…”
Section: Discussionmentioning
confidence: 51%
“…We also note that inherent molecular details of encaged guests such as ionic/nonionic and hydrophilic/hydrophobic guests greatly influence the cage dynamics. [2][3][4][5][6] Recently, hydrogen has received a great deal of attention in the hydrate community owing to its high potential for use in energy-related and many other issues. [7,8] Numerous studies concerning hydrogen storage using clathrate hydrates have been reported with much efforts aimed at increasing storage capacity, introducing unusual tuning effects by changes in concentration and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…16−18 The unique ionic guest−host interactions caused differences in the thermal expansivities of nonionic and ionic clathrate hydrates, and the γ-irradiated hydrates showed a smaller thermal expansivity and a larger dependence on secondary guest molecules. 19,20 While the thermal expansion behavior is important fundamental research, it also might be exploited in applications such as enhancing gas storage capacity by tuning the lattice dimensions. 21,22 Despite the importance and applicability of the structural effect of large guest molecules, which might have a significant impact on guest−host interactions, few studies have been conducted on this subject.…”
Section: ■ Introductionmentioning
confidence: 99%